Fucus vesiculosus phlorotannins: extraction, structural characterization and effects throughout the gastrointestinal tract - Catarino, Marcelo Dias (2021)
Marine macroalgae have a long tradition of usage and applications among the far Eastern populations, either for direct consumption and nutrition or for medicinal purposes. During the recent years, these marine organisms have received increasing popularity among the Western populations which are becoming aware of their potential to be exploited as a source of valuable bioactive compounds. Among these compounds are the phlorotannins, which are a group of phloroglucinol-derived phenolic compounds occurring exclusively on brown seaweeds and claimed for their promising health-promoting effects. Although several bioactive properties have been demonstrated for these compounds, there is still a long way to go before understanding the mechanisms behind them, and this is particularly true for the anti-inflammatory and antitumor properties of phlorotannins from Fucus vesiculosus. Moreover, little is known about the fate of these compounds when crossing the gastrointestinal tract. In this context, the aim of this work was to maximize the extraction of phlorotannins from this species for further characterization through UHPLC DAD-ESI-MSn analysis and evaluation of the bioactive properties that could be relevant from a performance point of view throughout the gastrointestinal tract, namely antioxidant, anti-inflammatory, antitumor and prebiotic effects. Through the response-surface methodology, the conditions determined for maximum recovery of F. vesiculosus phlorotannins were acetone 67% (v/v) in a proportion of 70 mL/g of seaweed powder at 25 °C. After an intermediate purification step, the phlorotannin-rich fraction (EtOAc) revealed a complex chromatographic profile composed of several fucols, fucophlorethols, fuhalols and several other phlorotannin derivatives. Additionally, three potential new phlorotannin derivatives, namely fucofurodiphlorethol, fucofurotriphlorethol and fucofuropentaphlorethol have been tentatively identified in this extract. Both the crude extract and EtOAc revealed good antioxidant activity, particularly against the nitric oxide radical, which is as very important player in the inflammatory signalling cascade. Indeed, strong anti-inflammatory activity was confirmed in a cellular system of inflammation using lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. From the EtOAc further subfractions with phlorotannins of increasing molecular weights were obtained and tested in the same cell line, revealing some differences between their anti-inflammatory activity which could be related to their complexity and molecular weight. A remarkably strong anti-inflammatory activity was observed for a particular subfraction, F2, characterized by the presence of a major phlorotannin derivative with molecular weight of 508 g/mol. At 200 µg/mL this subfraction was capable of inhibiting IκBα phosphorylation and degradation, and consequently blocking the pro-inflammatory signalling cascade at the transcriptional level. The EtOAc and some of its subfractions, namely F1 and F5, also demonstrated promising antitumor properties exerting a selective cytotoxic effect against gastric (MKN-28) and colon cancer cells (Caco 2 and HT-29) but not on normal cells. From these samples, F5, characterized for the presence of fucols, fucophlorethols, a fucofurodiphlorethol and eckstolonol, revealed the strongest effect in all the three tumor cell lines, exhibiting IC50 values of 56.3 ± 14.7, 97.4 ± 11.6 and 118.8 ± 19.7 µg/mL for MKN-28, Caco-2 and HT 29, respectively. Interestingly, while the EtOAc displayed this activity via induction of cell cycle arrest and activation of cell death mechanisms, the subfraction F1 only caused cell cycle arrest and the subfraction F5 only triggered cell death via activation of the apoptotic/necrotic mechanisms. Finally, these compounds were found to exert promising inhibitory capacity against some digestive enzymes, particularly α-glucosidase, in which the IC50 values were 45 a 250 times lower compared to acarbose, thus revealing a therapeutical potential for the treatment of type-II diabetes. However, similar to plant polyphenols, phlorotannins were found to be susceptible to degradation and loss of antioxidant activity during their passage through the gastrointestinal tract, with less than 15% of the initial total phlorotannins becoming bioaccessible and available for absorption. In turn, although the non-bioaccessible fraction of F. vesiculosus samples only contributed with a modest positive effect for the modulation of human microbiota, they could stimulate the production of propionate and butyrate,’pç which are two short-chain fatty acids with well established health-promoting properties for the host. In conclusion, this study not only allowed better understanding of the phlorotannin composition of F. vesiculosus, but also demonstrates that its extracts and/or purified fractions may have a relevant impact in the maintenance of a positive gastrointestinal health acting at different levels. Ultimately, this work contributes to the valorization of this species as a possible supply of natural compounds with great bioactive potential and applicability.